اليمين المتممة وأهميتها في االثبات المدني ]دراسة تحليلية مقارنة في االثبات المدني[ - د. تحسين حمد سمايل; م.م.كيفي مغديد قادر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Select the iraqs legislature evidence .and brought to same authorative full proof so that if there was the case judjr to end the rivalry and building rule them . and brought to some authoritative incomplete the therefor could not be realied upon and build a sentences . ie is not enough alone to prove the truth and complete conviction of the judje. But need to be supplemented by further evidence supporting its complement. The licenses of the Iraqi lrgislature judje in order to complete his conviction realied on the right complement upon the availability of controls, through direct to discount the evidence ,closer to the conviction of the judje or as required by the reality of the case and it is up to the discretion of the trial judje. With out depariting ftom the principle of neutrality, because the role of the judje begins following the submission of evidence and not before. Hence, we see the importance of the right complementary. And the importance of the text of the laws of evidence and the rest of the Iraqi and the other arab laws where the lead to end the conflict . and thus the lack of accumulation of the case to the court,as well as lead to the stability of the transactions and bring the truth of the factual truth and the return of the judicial the right of its owner.